2017
DOI: 10.1111/dmcn.13611
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of early magnetic resonance imaging to determine motor outcomes in infants born preterm: a systematic review and meta‐analysis

Abstract: Early magnetic resonance imaging (MRI) has reasonable sensitivity and specificity to determine later adverse motor outcomes and cerebral palsy (CP). Detection of infants who progressed to CP was stronger than motor outcomes. Global MRI scores determined adverse motor outcomes more accurately than white matter scores. Few studies report diagnostic accuracy of early MRI findings. Diagnostic accuracy is required to draw clinically meaningful conclusions from early MRI studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
(217 reference statements)
0
12
0
1
Order By: Relevance
“…However, clinical data to predict neurodevelopmental outcomes have only achieved modest prediction accuracy with an area under the curve (AUC) of 0.68 56 . Therefore, there is a need to examine the incremental value of brain MRI biomarkers over clinical factors [57][58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data to predict neurodevelopmental outcomes have only achieved modest prediction accuracy with an area under the curve (AUC) of 0.68 56 . Therefore, there is a need to examine the incremental value of brain MRI biomarkers over clinical factors [57][58][59][60][61] .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses are unfortunately hampered by heterogeneous study populations, variable scanning techniques and differences in radiological analysis and interpretation. One systematic review concluded that MRI should preferably be performed at term-equivalent age,32 while another found that structural MRI before 36 weeks postmenstrual age has reasonable sensitivity and specificity to predict outcome of cerebral palsy 33. Very early scanning has been found to have limited value for predicting outcome in a preterm cohort born at a median of 27+4 weeks and imaged at just 2 days of life 34.…”
Section: Translation Of Research Into Clinical Practicementioning
confidence: 99%
“…Например, в 2018 г. опубликованы результаты метаанализа 31 исследования диагностических возможностей раннего выполнения МРТ у недоношенных детей (< 36 нед) с использованием количественной оценки томограмм. Метаанализ показал, что глобальная оценка рано выполненной структурной МРТ обладает у недоношенных детей высокими чувствительностью и специфичностью как в отношении прогнозирования последующего развития ДЦП (100 и 93% соответственно), так и двигательных ограничений (89 и 98% соответственно) [49]. Глобальная оценка МРТ давала более точный прогноз двигательного исхода, чем оценка только белого вещества [49].…”
Section: прогностическое значение мр-находокunclassified